Subtract 2x from both sides of the equation:
-3y = 12 - 2x
Divide both sides by -3:
y = -4 + 2x/3
Rearrange the equation into y = mx + b form:
y = 2x/3 - 4
2007-01-06 16:30:04
·
answer #1
·
answered by Joy M 7
·
0⤊
0⤋
2x-3y=12 -3y= -2x+12 3y= 2x-12 y= (2/3)x - 4 Now....take your graph and on the vertical axis, place a dot at -4. Now, from that dot, go up 2 right 3 and place another dot. Then go up 2 and right 3 again. Also, from your point at -4, go down 2 and left 3 and place a dot. Go down 2 and left 3 again placing another dot. Now play the fun little game of connect the dots! =)
2016-05-23 02:01:05
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
All you need to do is this: subtract 2x from each side, then multiply by (-1/3), {which is the reciprocal of 3}, on each side (distribute through on the right side) to get the value of "y".
2x - 3y = 12
-2x..............-2x
-3y = -2x + 12
(-1/3)(-3y) = (-1/3)(-2x + 12)
y = 2/3x -4
2007-01-06 16:46:18
·
answer #3
·
answered by MegB 1
·
0⤊
0⤋
2x – 3y = 12
- 3y = -2x+12
-3/-3y = -2/-3x+12/-3
y = 2/3x - 4.....
2007-01-06 22:14:03
·
answer #4
·
answered by Akshitha 5
·
0⤊
0⤋
y = (12 - 2x)/3
y = (2/3)(6-x)
when x = 0
y = (2/3)(6 - 0) = (12/3) = 4
so you draw a point on the "y" axis at y=4
then, when y=0
x= -6
so you draw a point on the "x" axis at x=-6
then you join the points with a line and there you have it
=)
2007-01-06 16:33:26
·
answer #5
·
answered by IQ DOSON 2
·
0⤊
0⤋
You can solve for y and get the following:
y=2/3x-4
You can graph the function by creating an x,y table where you choose values for x and solve for y. Then use the points to create a graph.
2007-01-06 16:34:19
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
2x-3y=12
-3y=12-2x
y=(12-2x)/-3
y=2/3x-4
2007-01-06 17:45:28
·
answer #7
·
answered by heyheyhey 2
·
0⤊
0⤋
2x-3y=12
3y=12+2x
3y/3=12/3+2x
y=4+2x
^_^
tahts all what i know
2007-01-06 16:30:56
·
answer #8
·
answered by richard 2
·
0⤊
2⤋